Pelatihan Pengembangan Media Pembelajaran Flipbook untuk Guru Madrasah Ibtidaiyah - Amir Hamzah; Ines Tasya Jadiddah; Ayu Nur Shawmi; Amir Rusdi; Aquami Aquami; Miftahul Husni; Djoko Rohadi; Siti Fatimah (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2023)
This service aims to socialize the development of flipbook learning media at MI Nurul Qomar. The service method used is a development method that is oriented towards product development. The results of the dedication show that: socializing the development of flipbook learning media at MI Nurul Qomar, namely an explanation of the dynamics of the mentoring process for the various activities carried out, forms of technical action or program action to solve community problems. It also explains the expected emergence of social change, for example the emergence of new institutions, changes in behavior, the emergence of local leaders, and the creation of new awareness towards social transformation, and so on. This section also discusses the theoretical findings of the dedication process from the beginning to the occurrence of social change.